(untitled) (The Research of Medical Science Review, 2025)
Introduction and Objectives: Operation theater associated surgical sites infections have become a major concern globally diverting the attention of the health authorities towards the importance of disinfection in operation theatres. This study was carried out to compare the efficacy of Quaternary based compound and hydrogen peroxide containing compound in operation theater disinfection. Material and Methodology: A total of 288 Pre-fumigation and post fumigation samples comprising of swabs and agar plates were collected for both chemicals from General and Gynaecology operation theatres of District Headquarter Sheikhupura Hospital in a study duration of four months JulyNovember 2024. Samples were then processed for microbiological analysis using standard microbiological guidelines. Results: In first pre-fumigation, only (n=30) 41.6% of 72 samples were positive with Staphylococcus aureus 64.5% being predominant isolate from general in comparison to Coagulase Negative Staphylococci 48.5% from gynaecology operation theaters. Growth was reduced to (n=13) 18% post fogging using quaternary compound-based disinfectant with less than 10% growth observed for all microorganism collectively. During the 2nd cycle, less growth (n=28) 38.8% was observed pre-fumigation in comparison to 1st cycle with Staphylococcus aureus 48.3% and Staphylococcus epidermidis 54.7% being predominant isolates from the general and gynaecology operation theaters respectively. A reduction in positive samples (n=16)20.8% was observed following Hydrogen peroxide based disinfectant fogging with reduction below 13% in growth for all the isolates collectively. Conclusion: It was concluded that although, Quaternary compound-based disinfectant provided more promising outcomes as compared to hydrogen peroxide based chemical. Both reagents used were effective in reducing the microbial population to an extent no longer able to cause infection.